Humoral Acute Rejection in a Kidney Transplant Recipient with Idiopathic Thrombocytopenic Purpura - Ana Paola Rico-Portillo; José Ignacio Cerrillos-Gutierrez; Jorge Andrade-Sierra; Alfredo Gutiérrez-Govea; Enrique Rojas-Campos; Claudia Alejandra Mendoza-Cerpa; Benjamín Gómez-Navarro (Case Reports in Transplantation)
A 47-year-old male was diagnosed with chronic kidney disease (CKD) in 2011; idiopathic thrombocytopenic purpura (ITP) was also diagnosed in 2011 refractory to medical treatment and finally treated with splenectomy (2017) without relapses since that date, 5 blood transfusions, and 4 platelet apheresis in 2017. Renal transplant from a living related donor (brother), ABO compatible, crossmatch were negative, sharing 1 haplotype. Donor-specific anti-HLA antibody was negative. Graft function was stable until the 5th day and graft biopsy on the 6th day; thrombotic microangiopathy (TMA), C4D negative and inflammatory infiltration of polymorphonuclear leukocytes inside peritubular capillary, and anti-MICA antibodies were positive. The treatment used were plasmapheresis, intravenous immunoglobulin, and rituximab. Serum creatinine began to decrease since the 14th day, and by day 33, post-RT graft function was restored.